Diolefin complexes of transition metals as 'venus fly-trap' templates - Hill, Tania Nicola (University of the Free State, 2011)
The aim of this study was to gain a further insight into the bonding modes of 1,5-cyclooctadiene to various middle to late transition metal centres. The intension was to design a theoretical model of the influences of the variations of the metal centres and ligands on the “Venus fly-trap” system. Two principle geometric features were classified in the 1,5- cyclo-octadine when co-ordinated, i.e. the (bite) angle of the olefinic moieties to the metal centre, and the (jaw) angle, i.e. the dihedral angle between the two planes formed between the alkane ethylene groups. The latter mimicking the “jaws” of the Venus flytrap. A range of 1,5-cyclo-octadiene metal complexes were successfully synthesized and characterized via NMR and IR spectroscopy, the metal centers chosen were that of rhodium(I), platinum(II) and palladium(II). The ligands selected were divided into three categories namely · β-diketonato · β-enaminonato · tropolonato From each of these categories ligands were selected to vary the electron withdrawing or donating ability. Both symmetrical and non-symmetrical ligands were made use of, to see the influence of the nitrogen trans effect on the 1,5-cyclo-octadiene moiety. Finally, the tropolonato category added the influence of the smaller five membered metal chelate ring. A single crystal X-ray crystallographic study of the complexes was undertaken. The reported X-ray crystallographic structure determinations include the following complexes: [Pd(cod)(acac)]PF6 (1, Monoclinic P21/n, R = 3.59 %), [Pd(cod)(acac)]BF4 (2, Orthorhombic Pca21, R = 2.24 %), [Pd(cod)(thtfac)]PF6 (3, Monoclinic P21/n, R = 2.43 %), [Pd(cod)(thtfac)]BF4 (4, Monoclinic P21/n, R = 2.83 %), [Pd(cod)(tfacac)]PF6 (5, Triclinic P1 , R = 13.41 %), [Pd(cod)(hfacac)]PF6 (6, Monoclinic P21/c, R = 2.60 %), [Pt(cod)(acac)] (7, Orthorhombic Pca21, R = 1.75 %), [Pt(cod)(acac)]PF6 (8, Monoclinic P21/n, R = 3.02 %), [Pt(cod)(dbm)]BF4 (9, Triclinic P1), [Pt(cod)(thtfac)]BF4 (10, Monoclinic P21/n, R =2.80 %), [Pd(cod)(3Br-trop)]PF6 (11, Triclinic P1, R = 5.90 %), [Pd(cod)(3Br-trop)]BF4 (12, Triclinic P1, R = 3.40 %), [Pd(cod)(trop)]PF6 (13, Tetragonal P42bc, R = 4.08 %), [Pt(cod)(trop)]PF6 (14, Tetragonal P42/mbc, R = 3.45 %), [Pt(cod)(trop)]BF4 (14, Tetragonal P42bc, R = 2.91 %), [Pt(cod)(3Br-trop)]PF6 (16, Monoclinic C2/c, R = 4.38 %), [Pt(cod)(3Br-trop)]BF4 (17, Triclinic P1, R = 2.66 %), [Pd(cod)(NH-acac)]BF4 (18, Monoclinic P21/c, R = 2.24 %), [Pt(cod)(NH-acac)]BF4 (19, Monoclinic P21/c, R = 2.09 %), [Pt(cod)(NH-acac)]PF6 (20, Monoclinic C2/m, R = 3.88 %), [Pt(cod)(NMe-acac)]BF4 (21, Orthorhombic P212121, R = 1.50 %), [Pt(cod)(NMeacac)] PF6 (22, Monoclinic C2, R = 2.44 %), [Pt(cod)(NPh-acac)]BF4 (23, Monoclinic P21/n, R = 3.25 %), [Pt(cod)(NPh-acac)]PF6 (24, Triclinic P1, R = 3.29 %), [Rh(cod)(acac)] (25, Monoclinic Cc, R = 2.21 %), [Rh(cod)(dbm)] (26, Monoclinic Cc, R = 2.80 %), [Rh(cod)(thtfac)] (27, Monoclinic P21/n, R = 4.75 %) and [Rh(cod)(trop)] (28, Orthorhombic P212121, R = 1.39 %). The co-ordination geometry of the crystal structures was square planar, for palladium(II) and platinum(II) crystal structures resulting in a cationic charged species which was balanced with either BF4 - or PF6 - counter ions. Extensive hydrogen bonding was observed for the solid state structures with some interesting metal ring chelate interactions. The twist angle, the distortion from the square planar co-ordination geometry, for the crystal structures was found to be of a similar order. A theoretical DFT study was carried out on the group 7-11 transition metals with acetylacetone (Hacac), trifluoroacetylacetone (Htfacac), hexafluoroacetylacetone (Hhfacac), 4-aminopent-3-en-2-one (HNH-acac), 4-(methylamino)pent-3-en-2-one (HNMe-acac), 4-anilinopent-3-en-2-one (HNPh-acac), tropolone (Htrop) and tribromotropolone (H3Br-trop). The comparison of the calculated structures with the Xray crystal structures was found to be in good agreement with R-values of greater than 98 %. The molecular orbitals showed the influences of the π orbital delocalization and the bonding orbitals of the cyclo-octadiene with the various transition metal centres and provided an easy graphical method to compare both the variations of ligands and metal centres. Both the molecular orbital energies and band gap energies were presented and reflected the changes in the cyclo-octadiene complexes. A push-pull effect was observed though the use of the “core” co-ordination geometry, where the metal displays a lateral movement within the co-ordination area (Atot). The bite and jaw angles were determined for all the theoretical structures as well as the solid state crystal structures obtained. A maximum opening of c.a. 15° for the β-diketonato complexes while both the β-enaminonato and tropolonato complexes have a c.a. 14° variation in the jaw angle affected by both the metal and trans ligand manipulations.

Die doelwit van hierdie studie was om ‘n meer breedvoerige insig te verkry oor die verbindings van 1,5-siklo-oktadieen met verskeie middel- tot laat oorgangs metal kerne, met die doel om ‘n teoretiese model te skep. Hierdie model sal die invloed van die wisseling van die metal kerne en die ligande op die “Venus fly-trap” sisteem illustreer. Twee hoof geometriese karakter eienskappe was geklassifiseer wanneer die siklooktadieen gekoordineer is, (a) die (bite) hoek van die olefeniese gedeeltes na die metal kern, en (b) die (jaw) hoek wat die dihidriese hoek tussen die twee oppervlakkes is wat gevorm het tussen die alkaan eteen groepe. Laasgenoemde naboots die “jaws” van die “Venus fly-trap”. ‘n Reeks van 1,5-siklo-oktadieen metal komplekse was suksesvol gesintetiseer en geklassifiseer met behulp van KMR en IR spektroskopie. The metal kerne wat gekies was, is rhodium(I), platinum(II) en palladium(II). Die ligande wat gekies was kan gegroepeer word in drie afdelings, naamlik: · β-diketonato · β-enaminonato · tropolonato Ligande uit hierdie kategorieë is gekies om elektron ontrekking of skenking vermoeë te varieer. Beide simmetries en nie-simmetriese ligande is gebruik om die invloed van die stikstof trans effek op die 1,5-siklo-oktadieen gedeelte. Laastens het die tropolonato kategorie die invloed van die kleiner vyf-lid metal chelaat ring bygedra. ‘n Enkel kristal x-straal kristallografiese studie van die komplekse was ook onderneem. Die x-straal kristallografiese struktuur bepalings wat verkryg was het die volgende komplekse ingesluit: [Pd(cod)(acac)]PF6 (1, Monoklien P21/n, R = 3.59 %), [Pd(cod)(acac)]BF4 (2, Orthorombies Pca21, R = 2.24 %), [Pd(cod)(thtfac)]PF6 (3, Monoklien P21/n, R = 2.43 %), [Pd(cod)(thtfac)]BF4 (4, Monoklien P21/n, R = 2.83 %), [Pd(cod)(tfacac)]PF6 (5, Triklien P1 , R = 13.41 %), [Pd(cod)(hfacac)]PF6 (6, Monoklien P21/c, R = 2.60 %), [Pt(cod)(acac)] (7, Orthorombies Pca21, R = 1.75 %), [Pt(cod)(acac)]PF6 (8, Monoklien P21/n, R = 3.02 %), [Pt(cod)(dbm)]BF4 (9, Triklien P1), [Pt(cod)(thtfac)]BF4 (10, Monoklien P21/n, R =2.80 %), [Pd(cod)(3Br-trop)]PF6 (11, Triklien P1 , R = 5.90 %), [Pd(cod)(3Br-trop)]BF4 (12, Triklien P1 , R = 3.40 %), [Pd(cod)(trop)]PF6 (13, Tetragonal P42bc, R = 4.08 %), [Pt(cod)(trop)]PF6 (14, Tetragonal P42/mbc, R = 3.45 %), [Pt(cod)(trop)]BF4 (14, Tetragonal P42bc, R = 2.91 %), [Pt(cod)(3Br-trop)]PF6 (16, Monoklien C2/c, R = 4.38 %), [Pt(cod)(3Br-trop)]BF4 (17, Triklien P1, R = 2.66 %), [Pd(cod)(NH-acac)]BF4 (18, Monoklien P21/c, R = 2.24 %), [Pt(cod)(NH-acac)]BF4 (19, Monoklien P21/c, R = 2.09 %), [Pt(cod)(NH-acac)]PF6 (20, Monoklien C2/m, R = 3.88 %), [Pt(cod)(NMe-acac)]BF4 (21, Orthorombies P212121, R = 1.50 %), [Pt(cod)(NMe-acac)]PF6 (22, Monoklien C2, R = 2.44 %), [Pt(cod)(NPhacac)] BF4 (23, Monoklien P21/n, R = 3.25 %), [Pt(cod)(NPh-acac)]PF6 (24, Triklien P1, R = 3.29 %), [Rh(cod)(acac)] (25, Monoklien Cc, R = 2.21 %), [Rh(cod)(dbm)] (26, Monoklien Cc, R = 2.80 %), [Rh(cod)(thtfac)] (27, Monoklien P21/n, R = 4.75 %) and [Rh(cod)(trop)] (28, Orthorombies P212121, R = 1.39 %). Die gekoördineerde geometrie van die kristal strukture was vierkantige planêr vir beide die palladium (II) en platinum (II) kristal strukture. Hierdie koördinasie lei tot ‘n kationiese gelaaide spesie wat gebalanseerd is met BF of BF teenstellende ione. ‘n Oorgroote merderheid waterstof bindings was waargeneem vir die soliede toestand strukture, asook noemswaardige metal ring chelaat interaksies. Die “twist” hoek, wat die vervorming van die vierkantig planêre koördinasie geometrie vir die kristal strukture is, is bevind om van dieselfde orde te wees. ‘n Teoretiese DFT studie is uitgevoer op die groep 7-11 oorgangs metale met asetielasetoon (Hacac), trifluoroasetielasetoon (Htfacac), hexafluoroasetielasetoon (Hhfacac), 4-aminopent-3-en-2-one (HNH-acac), 4-(methylamino)pent-3-en-2-one (HNMe-acac), 4-anilinopent-3-en-2-one (HNPh-acac), tropolone (Htrop) and tribromotropolone (H3Br-trop). Die R-waarde wat verkry is wanneer die x-straal kristal strukture met die berekende teoretiese strukture vergelyk was, was > 98 %. Die molekulêre orbitale dui die invloed van die gedelokaliseerde π orbital en die verbindings orbital van die siklo-oktadieen met die verskillende oorgangs metal kerne aan. Die molekulêre orbitale voorsien ‘n maklike grafiese metode vir die vergelyking van beide die ligande en die metaal kerne. Beide die molekulêre orbitale energieë en die “band gap” energieë is teenwoordig en reflekteer die veranderinge in die siklo-oktadieten komplekse. ‘n Aftoot-aantrek effek was waargeneem deur die gebruik van die “core” gekoordineerde geometrie, waar die metal ‘n sywaartse beweging binne die koordinasie area getoon het. Die bite en jaw hoeke was bereken vir al die teoretiese strukture, asook vir die vaste toestand kristal strukture. ‘n Maksimum opening van c.a. 15° vir die β-diketonato kompleks is waargeneem, terwyl vir beide die β-enaminonato en tropolonato komplekse ‘n 14° variasie in die jaw hoek waargeneem is wat geaffekteerd is deur metaal en trans ligand manipulasies.
Thesis (Ph. D. (Chemistry))--University of the Free State, 2011
Keywords: Transition metals; Hydrogen bonding; Crystallography; Synthesis; Crystallography; Theoretical calculations; Tropolone; Rhodium; Platinum and palladium complexes; Transition metals; Hydrogen bonding interactions; Metal chelate ring interactions; β-diketone; β-enaminone